Schön / Nur Hadirah Samsulrizal ... [et al.] - Samsulrizal, Nur Hadirah; Aris, Nurshuhadah; Azizi, Nurul Syafiqah; Yusof, Anis Batrisyia; Aliyasak, Muhammad Alif Haikal (2025)
Schön Sdn. Bhd. is an establishment categorized in the beauty industry that focuses on providing a life changing beauty-solution via our makeup product, that is carefully crafted to perfection. This business plan will outline the market strategy, operations plan, and financial details for ‘Schön’. Schön is located in Subang Jaya, Selangor after taking various reasons into account. Such as suitability of the environment, product transportation, size and safety of the area for long term use and all product related details. As it is preferable for the identity of the company’s members to be separated from the company’s, Private Limited Company (SDN BHD) is incorporated as our business identity which makes our company name ends with Sdn Bhd. Schön creates a product that solves a problem which women wearing makeup often face. This includes feeling like wearing or removing makeup is time consuming, as well as feeling lazy when they have to remove it especially after a long day when they just wanted to rest or when it is time to perform prayers while going out. Our foundation is infused with a unique combination of healthy and intelligent ingredients that allows it to be left on the face without having to remove it while posing no harm to skin. Which means, accidentally sleeping with makeup on is no longer an issue. Not only that, if it is required for a person to remove their makeup for example to perform prayers, our product can turn into a face wash by itself. There is no need to carry a makeup remover or cleanser as the makeup itself can be a face wash. Our target market will be focusing on women as they will be the most interested in the solution we provided. The sole reason for the establishment of the product and company is to be the leading company that first provides a solution to these problems, prioritizing women and their needs which will eventually lead to a new evolution of the beauty industry and encouraging a more creative approach to create a new product in the future. The owners have contributed to a lot of things such as brainstorming the idea itself, planning the details to produce the product and establishing the company while considering all possibilities to ensure smooth operations and successfully gained financial support by loan, amounting to RM 58 000 which also covers our initial capital to start the business. From the business plan, the expected sales forecast for year 1, 2 and 3 will be RM 404 493, RM 465 167 and RM 558 201 respectively. With each unit being sold for RM37, and 912 units of product being produced every month, a projected profit of RM 299 265, RM 344 168, and RM 413 711 will be obtained for year 1, 2 and 3 respectively. The team managing the market plan, operational plan, administration and financial details play a vital role in our company act as the key management teams that are also the backbone of the company which holds the vision and mission of the company strongly to ensure a success in achieving it.